SALUANG PANJANG (PATIAK TIGO) SEBAGAI JEJAK MEMORIS KOLEKTIF DI NAGARI LUAK KAPAU KECAMATAN PAUAH DUO KABUPATEN SOLOK SELATAN STUDI REGENERASI MUSIK MINANGKABAU (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
This study examines the regeneration of Saluang Panjang traditional art in Nagari Luak Kapau, South Solok Regency, which has experienced a decline in interest among the younger generation due to social change. The research employs a qualitative descriptive approach using observation, interviews, and documentation techniques. The findings indicate that Saluang Panjang is still recognized as part of the community’s cultural identity, although the frequency of its performances has decreased. The performances are presented in a simple form, involving a saluang player and a singer performing traditional pantun with distinctive South Solok expressions, and the regeneration process occurs through oblique transmission directly from the artists.